Origin of Tropical Diversity: From Clades to Communities - James Edward Richardson (Frontiers Research Topics, 2017)
In this volume we aimed to assess progress in determining the processes by which current patterns of tropical biodiversity were established and are maintained. Tropical regions are highly species-rich and we present studies that have improved our understanding of the generation of that diversity at local, regional and global scales. We demonstrate how diverse fields from molecular phylogenetics, phylogeography, palaeontology and palaeoecology continue to improve our understanding of the natural history of the tropics.